A 1‐year and 4‐month‐old child with mucopolysaccharidoses type II: A clinical case report from Ethiopia. Issue 11 (22nd November 2021) - Deribessa, Solomie Jebessa; Bisrat, Mekdes Endale; Terefework, Zewdu; Quinonez, Shane C.
Abstract: Mucopolysaccharidoses (MPSs) are a class of lysosomal storage disorders resulting in progressive disease manifestations and are caused by pathogenic variants in genes coding for enzymes needed to degrade glycosaminoglycans. While most of the seven MPSs are autosomal recessive disorders, MPS II, also known as Hunter syndrome, is inherited in an X‐linked recessive manner and is the most common MPS. Here, we report a 1‐year and 4‐month‐old boy who presented with delayed developmental milestones, back deformity, and left scrotal swelling noticed by parents at one year of age. He has coarse facial appearance with macrocephaly, widened wrists, congenital dermal melanocytosis on his back, kyphotic deformity in the thoracolumbar area and left‐sided inguinal hernia all consistent with a suspected MPS II diagnosis. The MPS II diagnosis was subsequently confirmed with genetic testing of the IDS gene. To our knowledge, this is the first case of MPS II reported from Ethiopia. This case shows the importance of early clinical recognition of genetic conditions and the utility of genetic testing for confirmation. The diagnosis provided important surveillance and natural history information for the patient's providers and family. Abstract : Mucopolysaccharidosis type II/Hunter syndrome is an X‐linked recessive lysosomal storage disorder. We report a 1‐year and 4‐month‐old boy with coarse facial appearance, macrocephaly, dermal melanocytosis, widened wrists, kyphotic deformity, and left‐sided inguinal hernia, consistent with MPS II, subsequently confirmed with genetic tests. There is no family history, parents are counselled.